2012
DOI: 10.1111/j.1540-627x.2012.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Growing SMEs More Market-Oriented and Brand-Oriented?

Abstract: The aim is to examine whether growing, stable, and declining small and medium‐sized enterprises (SMEs) differ from one another in terms of market orientation and brand orientation. The results show that growing SMEs have adopted market and brand orientations to a greater extent than have the stable or declining ones. They also suggest that these orientations can prove to be helpful in achieving different kinds of growth goals. Thus, in order to support the growth of SMEs, more information and training should b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 56 publications
(127 reference statements)
3
87
1
6
Order By: Relevance
“…Organization's hierarchy, departments, degree of formalization, inter-functional coordination, roles and responsibilities, and top down bottom up integration (Webster & Keller, 2004). Reijonen et al (2012) results strongly suggested that growing SMEs were more brand oriented where inter-functional cooperation was also high.…”
Section: Internal Environmentmentioning
confidence: 73%
“…Organization's hierarchy, departments, degree of formalization, inter-functional coordination, roles and responsibilities, and top down bottom up integration (Webster & Keller, 2004). Reijonen et al (2012) results strongly suggested that growing SMEs were more brand oriented where inter-functional cooperation was also high.…”
Section: Internal Environmentmentioning
confidence: 73%
“…Thus, brand orientation emphasizes the strategic significance of branding activities, and is therefore seen as a resource that may shape a firm's strategic direction . As an inside-out strategic posture, brand orientation enables a firm to develop and sustain a shared value with core stakeholders (i.e., customers and employees) to generate superior performance (Napoli, 2006;Reijonen, Laukkanen, Komppula, & Tuominen, 2012). Given that brand orientation encapsulates a firm's long-term strategic goal, it helps define and cement relationships within the firm (Napoli, 2006;Urde, 1994;Urde et al, 2013).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Future studies should consider studying SME brand in other industry to further validate our findings. Besides, literatures had indicated there is dearth of branding studies in the context of SME brand in comparison to global/ big brand (Agostini et al, 2014;Asamoah, 2014;Reijonen, Laukkanen, Komppula, & Tuominen, 2012;Spence & Essousi, 2010). Hence, we strongly urge more researches on other SME brands to contribute on the SME branding literature.…”
Section: Limitation and Future Researchmentioning
confidence: 99%
“…Moreover, it is important to examine these relationships on SME brands because it may contribute different result as compared to global/ big brands (Berthon et al, 2008;Caloghirou et al, 2014;Upadhyay, Jahanyan, & Dan, 2011). Besides, there has been lack of studies on SME brand loyalty (Asamoah, 2014;Centeno et al, 2013;Krake, 2005;Reijonen, Laukkanen, Komppula, & Tuominen, 2012). Therefore, this study will fill this gap by developing a conceptual framework to investigate the relationships between brand experience, brand trust, and customer loyalty from the perspective of SME brands.…”
Section: Introductionmentioning
confidence: 99%